2017
DOI: 10.3389/fpubh.2017.00277
|View full text |Cite
|
Sign up to set email alerts
|

Screening Novel Molecular Targets of Metformin in Breast Cancer by Proteomic Approach

Abstract: Metformin is a commonly prescribed antihyperglycemic drug, and has been investigated in vivo and in vitro for its effect to improve the comorbidity of diabetes and various types of cancers. Several studies investigated the therapeutic mechanisms of metformin on cancer cells, but the exact mechanism of metformin’s effect on the proteomic pathways of cancer cells is yet to be further investigated. The main objective of our research line is to discover safe and alternative therapeutic options for breast cancer, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 71 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…Its hyper-activation can lead to excessive tumor cell proliferation, inhibition of apoptosis, angiogenesis, invasion and metastasis (40)(41)(42). For our part, we suggest that MET treatment may play a noticeable role in modulating cell signaling activation related to PI3K/Akt/mTOR pathways in breast cancer cells, that corroborates recent reports (43,44).…”
Section: Discussionsupporting
confidence: 90%
“…Its hyper-activation can lead to excessive tumor cell proliferation, inhibition of apoptosis, angiogenesis, invasion and metastasis (40)(41)(42). For our part, we suggest that MET treatment may play a noticeable role in modulating cell signaling activation related to PI3K/Akt/mTOR pathways in breast cancer cells, that corroborates recent reports (43,44).…”
Section: Discussionsupporting
confidence: 90%
“…2f, metformin may reduce cisplatin resistance induced by TNBC-EVs in normal tissues via RAD51. In addition, it was reported that metformin selectively targeted cancer stem cells and also induced apoptosis in human breast carcinoma cell line MCF-7 with minimal toxicity to MCF10A [52, 53]. Furthermore, metformin prevented normal cell apoptosis against cisplatin-induced ototoxicity and nephrotoxicity in auditory cell and tubular cell [54].…”
Section: Discussionmentioning
confidence: 99%
“…For our part, at the concentration of MET used (2.5 mM) we found a modest and non significant reduction of the PI3K/Akt activation in breast cancer cells. However, several studies reported that metformin reduced the survival and proliferation rate of breast cancer cells through the inhibition of PI3K/Akt signaling pathway [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%